Research on Measures to Limit Short-Circuit Current by Renovating the Equipment of the Power Grid - Shuqin Sun; Guanghao Zhou; Zaihua Li; Xiaojun Tang; Yuguang Zhou; Zhenghai Yuan (Energies)
This paper addresses the increasingly severe issue of exceeding short-circuit current limits brought about by the rapid development of large power grids. It investigates the principles of short-circuit current control and methods to limit short-circuit current through the modification of grid equipment. Building on the current state of research, this study introduces different types of impedances to analyze their effects on the control of short-circuit currents, thereby exploring the principles of short-circuit current control based on the composition of actual grid short-circuit currents. Regarding the issue of controlling short-circuit current levels in large power grids, a detailed analysis is conducted of the operational principles, advantages, and disadvantages of five types of modified grid equipment for limiting short-circuit current: high-impedance generators, high-impedance transformers, current-limiting reactors, fault current limiters (FCLs), and a generator–transformer–line group unit. This study identifies the applicable conditions for each short-circuit current-limiting measure and presents specific engineering simulation cases to validate their effectiveness in limiting short-circuit currents, thus determining the control effects of each limiting measure. The results indicate that this research plays an important role in controlling short-circuit currents in power systems, maintaining the safe and stable operation of power systems, and improving the structural framework of power systems.